Novel ABCA3 mutations as a cause of respiratory distress in a term newborn - Gonçalves, JP (2013)
We report here the case of a term female newborn that developed severe respiratory distress soon after birth. She was found to be a compound heterozygote for both novel mutations in the ABCA3 gene. ABCA3 deficiency should be considered in mature babies who develop severe respiratory distress syndrome.